Polarization Observables in WZ Production at the 13 TeV LHC: Inclusive Case - Baglio, Julien; Le, Duc Ninh (Communications in Physics, 2020)
We present a study of the polarization observables of the W and Z bosons in the process \(p p → W^± Z→ e^± u_e μ^+μ^-\) at the 13 TeV Large Hadron Collider. The calculation is performed at next-to-leading order, including the full QCD corrections as well as the electroweak corrections, the latter being calculated in the double-pole approximation. The results are presented in the helicity coordinate system adopted by ATLAS and for different inclusive cuts on the di-muon invariant mass. We define left-right charge asymmetries related to the polarization fractions between the \(W^+ Z\) and \(W^- Z\) channels and we find that these asymmetries are large and sensitive to higher-order effects. Similar findings are also presented for charge asymmetries related to a P-even angular coefficient.